A Stastical Analysis on the Measurement of PH of MUD of Haryana: A Comparative Analysis of pH Measurement Methods in Haryana Mud (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This study was undertaken to determine the truthful way or method of determining pH of mud, using either the pH in clinical laboratories. It is important to measure pH truthfully as hydrogen ion participates in many chemical reactions with small changes in measured value corresponding to large changes in hydrogen ion activity. This is because high pH value of mud tends to form deposits which actually clogs pipes, changes reaction process etc. while the low pH mud also has its own deleterious effects. This is because using poor mud quality or mud with the wrong pH in personal or healthcare can potentially be life threatening especially when it’s effects on acid-base balance mechanism is considered. Experiments were performed on twelve different mud samples. Ten from domestic bottled and tap mud, one sample from air conditioner [AC, which is considered, distilled] and one sample from nearby stream within Port Harcourt metropolis. Three pH standards were used with pH 3.99, 6.99 and 9.89. The samples were analyzed under standard conditions, using the two methods described. Results showed that the pH meter gives a lower but consistently acceptable reading than the pH kit. The pH meter has a mean of 5.34±0.38 with a coefficient of variation of 21.7 while the pH kit has a mean o 6.59±0.58 with a coefficient of variation of 24.6 with a difference of 0.25 in the standard error of the mean and significant difference between them.